CLIL and CALL for a teacher's expertise: an international training experience - Letizia Cinganotto; Daniela Cuccurullo (Firenze University Press, 2016)
The paper deals with the link between Content and Language Integrated Learning (CLIL) and Computer Assisted Language Learning (CALL), that is the use of ICT to enhance language teaching-learning and the teaching of subject content in a foreign language. Starting from this background, the paper describes an online training initiative promoted by the authors within an international community of peers, made up of teachers, trainers and educators from all over the world, named "Techno-CLIL for EVO 2016". The initiative was aimed at supporting and guiding participants to discover and experiment digital tools for CLIL lessons, offering the opportunity to share ideas, materials, good practices in an international perspective. Particular attention is devoted to the personal and professional enrichment and growth this training pathway may have helped the 5.000 participants to achieve. CLIL e CALL nell'expertise del docente: un'esperienza di formazione internazionale Il contributo focalizza l'attenzione sulla correlazione tra Content and Language Integrated Learning (CLIL) e Computer Assisted Language Learning (CALL), cioè l'uso delle tecnologie per una maggiore efficacia dell'insegnamento-apprendimento delle lingue o di contenuti disciplinari veicolati in lingua straniera. Partendo da questo background, il contributo descrive una iniziativa di formazione online in lingua inglese promossa dalle autrici all'interno di un contesto internazionale, costituito da una comunità di pratica di docenti, formatori, educatori di tutto il mondo, denominata "Techno-CLIL for EVO 2016". L'iniziativa mirava a sensibilizzare e guidare i partecipanti nella scoperta e sperimentazione della didattica CLIL in modalità digitale, offrendo l'opportunità di un confronto ed uno scambio di idee, materiali, buone pratiche in una prospettiva internazionale. Particolarmente significative le ricadute che questo percorso ha comportato per i circa 5.000 partecipanti in termini di expertise, competenze professionali e arricchimento personale.